Are central nervous system drugs displaying anti-inflammatory activity suitable for early treatment of COVID-19? - Grieb, Paweł; Rejdak, Konrad (Folia Neuropathologica, 2021)
The majority of COVID-19 cases are only mildly or moderately symptomatic, but in some patients excessive inflammatory response becomes the dominant factor of disease progression to the advanced stage, with high mortality. Treatment with anti-inflammatory drugs either does not prevent disease progression (non-steroidal anti-inflammatory drugs [NSAIDs], colchicine), or is recommended only at the advanced disease stage (dexamethasone). Fluvoxamine and amantadine are drugs used to treat neurological and psychiatric diseases. Fluvoxamine is a selective serotonin uptake inhibitor, whereas amantadine is an old antiviral variably influencing brain neurotransmitter systems, and repurposed to Parkinson’s disease. Both drugs are agonists of sigma-1 receptors located in the endoplasmic reticulum, which effect seems responsible for their anti-inflammatory activity. Moreover, amantadine was found to dampen the expression of cathepsin-L, a lysosomal enzyme implicated in SARS-CoV-2 virus entry to target cells. In two small controlled clinical trials, early treatment of SARS-CoV-2-infected persons with fluvoxamine fully prevented COVID-19 symptoms. Anecdotal evidence shows that amantadine may be similarly effective. Both drugs are easily available, inexpensive and have favorable safety profiles. Clinical trials evaluating their efficacy as much-needed post-exposure prophylaxis and early treatment of COVID-19 are ongoing.